Rationale and design of an exercise intervention for patients with cancer cachexia: protocol for a one-year follow-up prospective study (2CAPA) - Romane Peyrachon; Cindy Richard; Brigitte Gelein; Astrid Lièvre; Nathalie André; Karl Chaory; Amélie Rébillard (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The prevalence of cancer with cachexia is rising sharply. More than 80% of digestive cancer patients are affected by cancer cachexia. Cachexia leads to weight loss, and reduces quality of life, cancer treatment response and survival. Exercise could counteract the deleterious effects of cachexia. The 2CAPA study aims to assess the effectiveness of a 12-week exercise program on various symptoms associated with cancer cachexia, including food intake, body composition, physical fitness, physical activity levels, Health-Related QoL (HRQoL) and fatigue. Additionally, it seeks to examine compliance with the exercise program, identify barriers to regular exercise and determine how compliance influences physical and psychological effects. Furthermore, we will determine the maintenance of physical activity levels and the effects post-program for one year follow-up on cachexia-related symptoms. Methods This study will include 31 cancer patients with cachexia. Participants will receive a supervised exercise program lasting 12-weeks with two sessions per week combining endurance and resistance training. Our outcomes include food intake, anthropometric parameters, physical performances, and physical activity levels, HRQoL, and fatigue, at baseline, at the end of the 12-week exercise program, and at 3-, 6- and 12- months post-intervention. Outcomes will be compared between cancer patients with cachexia and a control group of 31 non-cachectic patients. Conclusion This study is the first prospective, monocenter, real-life investigation designed to assess the efficacy of a supervised 12-week exercise program on physical and psychological cachexia-related symptoms at the end of the program and then during a one-year follow-up. Moreover, our study will identify compliance and barriers to regular exercise for patients with cachexia. Our results will contribute to the management of cachexia-associated with cancer and provide recommendations to ensure that the program achieves the greatest possible effects and the greatest possible compliance. Ethics and dissemination This study was reviewed and approved by Ethics Committee of Rennes (N°2023-039). The findings will be disseminated to the scientific and medical community via publications in peer-reviewed journals and conference presentations. Trial registration number NCT06323733, 21/03/2024.